Leucemia linfoblástica aguda em crianças e adolescentes: perfil clínico e desfechos da doença - Felizari, Giovana Bonessoni (2020)
BACKGROUND: The most frequent cancer in children and adolescents is acute leukemia, representing about 30% of cancer cases in this population. Acute leukemias of the lymphoid cell line are the most common and correspond to 80% of cases. The pathophysiology of the disease consists of a disorder in cell hematopoiesis - specifically in the production of cells of the lymphoid lineage - when young cells proliferate, the blasts, which infiltrate the marrow and cause the disease. In the past few decades, patient survival has increased to about 90% and this has been due to targeted therapy and improved supportive care. OBJECTIVES: To describe the epidemiological and clinical profile of children and adolescents diagnosed with acute lymphoblastic leukemia, treated at the Children's Oncological Center, located in a tertiary hospital in the city of Passo Fundo - RS. METHODS: Retrospective cohort study, using secondary data from all patients aged between 0 and 19 years who had the diagnosis and treatment of ALL from January 2015 to January 2020. The study was approved by the Ethics Committee and Local search. RESULTS: The sample consisted of 48 patients of both sexes, with a prevalence of males (62.5%), patients aged <9 years (58.3%), Caucasian (83.4%), ALL from B cells (87.5%) and the main outcome observed was prolonged disease remission (77,2%). CONCLUSION: The characterization of ALL studied patients at the center, in their majority, was in agreement with the literature, as well as the main signs and clinical symptoms, defining what is important for the knowledge of the population particularities in order to improve the results of treatments and survival rates and prolonged remission of the disease.